Choosing Jordanianness - Yousef Barahmeh; Jona Fras (Revue des Mondes Musulmans et de la Méditerranée)
This article investigates the dialogic construction of Jordanian identity discourse as reflected through the production of everyday discourse on the nation, following both Anderson’s (1983) idea of nation as a ‘socially constructed community’ and Billig’s (1995) concept of ‘banal nationalism’. Against both the narrative of unifying regime initiatives and Transjordanian ethnic exclusivism, we delve deeper into the narrative of everyday nationalism, revolving around everyday practices through which ordinary people ‘choose the nation’ by means of popular culture. We draw on nationalist songs, memes, graffiti and social media hashtags where Jordanian ‘everyday nationalism’ involves a dialogic construction of identity that can draw on either Transjordanian or Palestinian symbolism. This discourse of nationhood is dialogic through its constitutive, if oppositional, relationship between symbols representing Transjordanians and Jordanians of Palestinian origin. Here, 'choosing the nation’ goes beyond simple narratives of unity or exclusion, reproducing constitutive identity fractures yet remaining dependent on their continued existence.